APPLICATION OF THE RAPID APPLICATION DEVELOPMENT METHOD TO THE BAZNAS ZAKAT RECEIPT INFORMATION SYSTEM IN KARAWANG - Muhamad Tabrani; Hananda Priyandaru; Suhardi - (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
Zakat is one of the pillars of Islam, it is obligatory for every Muslim to do it. In fact, there are still many Muslims who do not understand the types of zakat, zakat calculation, payment and processing of zakat, causing them forget to pay zakat. Moreover, in this modern era, people want do anything fast and practical. Even though if every Muslim and Muslimah is willing to pay zakat diligently, of course it can help improve the economy for the middle to lower class society. And of course zakat must be issued and processed according to the established rules. Information system development uses the Rapid Application Development System method, starting from the requitment planning, system design, and implementation phases, as result an objective information system. This website-based information system was built with HTML, CSS, Boostrap and PHP programming languages ​​and for the database uses MySQL and for its web service uses Apache